Food and fluid intake and palliative sedation in palliative care units: A longitudinal prospective study. (February 2014) - Claessens, Patricia; Menten, Johan; Schotsmans, Paul; Broeckaert, Bert
<x content-type="archive" xml:space="preserve">Abstract</x> Background Divergent opinions exist on what is correct and morally acceptable when it comes to the management of patients who are terminally ill and unable to maintain their own nutritional and hydration needs. This issue becomes even more problematic when it concerns patients for whom palliative sedation is considered. The aim of this study is to describe the evolution of oral and artificial food and fluid intake of patients residing in Flemish palliative care units and the possible effect of palliative sedation. Methods A prospective longitudinal and descriptive design was used. Each patient admitted in one of the eight participating units was included if they met the inclusion criteria and gave written informed consent. Results Two hundred and sixty-six patients were included. The incidence of palliative sedation was 7.5%.The oral food and fluid intake of these patients decreased during their stay and was reduced to a minimum a few days before death. With regard to the artificial food/fluid intake, this study reveals that only 28% of patients received artificial food and/or fluid. Moreover, it shows that the withdrawal is not a standard policy but is always based on a profound and individual decision-making process. An effect of initiating palliative sedation on the fluid intake is found, but is of no clinical relevance, in the sense that it would shorten the life of the patient. Conclusions This longitudinal prospective study does not support the argument that palliative sedation amounts to 'slow euthanasia' because it entails the withholding or withdrawing of substantial amounts of food and or fluids, thus having a clear life-shortening effect. This study shows that palliative sedation, in specialized palliative care units, is not slow euthanasia but advanced symptom control during the final days of terminally ill patients' lives who are confronted with refractory suffering.